Perilaku Bullying Verbal Pada Peserta Didik Kelas VIII dan IX SMP Negeri 3 Satu Atap Bojong - Nasikhatun Nafisah; Mazro Atus Saadah; Putri Anggriani (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
This research is about Verbal Bullying Behavior in Class IX Students of SMP Negeri 3 Satu Atap Bojong. The problem formulations in this study are: (1) what causes individuals to be verbally bullied? (2) what is the impact of verbal bullying on the victim? (3) what is the impact of verbal bullying on the perpetrator? (4) what are the efforts of counseling teachers in dealing with victims of verbal bullying? (5) what are the efforts of counseling teachers in preventing verbal bullying committed by students? This study aims to describe and find out about the forms of verbal bullying behavior that occur in class IX students of SMP Negeri 3 Satu Atap Bojong. quite low category. (1) Family factors as the main cause of individuals committing verbal bullying with the category